Alat Inovatif untuk Mengukur Kekuatan Tangan pada Kesehatan Anak: Pengembangan dan Evaluasi - Eny Erlinda Widyaastuti; Dudella Desnani Firman Yasin; Arif Rahman Aceh; Nurma Zela Gustina (An Idea Health Journal, 2026)
Background: The musculoskeletal system plays a crucial role in movement and balance, which are coordinated with the nervous system. Therefore, muscle strength has both physiological and clinical implications. Furthermore, the musculoskeletal system, including muscles, undergoes developmental stages with age. Consequently, significant differences in the musculoskeletal system between children and adults are evident. This affects differences in muscle strength measurements, particularly those related to the tools used, which, in turn, influence anthropometric measurements. Methods: This study used a quasi-experimental design involving 70 child respondents aged 6–12 years to evaluate the extent to which the developed tool produces consistent measurements of left and right hands through bilateral correlation, using a simple hand muscle strength measurement tool that can be effectively used in the pediatric population. Evaluation measurement uses the Intraclass Correlation Coefficient (ICC). Result: The reliability test using the ICC with a two-way mixed model and absolute agreement type showed that measurements at the 7 cm position demonstrated good reliability, with a single-measure ICC of 0.774 and an average-measure ICC of 0.872.2. The measurements at the 8 cm position demonstrated higher reliability, with a single-measure ICC of 0.870 (95% CI: 0.797–0.918), which is considered good, and an average-measure ICC of 0.931 (95% CI: 0.887–0.957), which is considered very good. Furthermore, the Cronbach's Alpha value for the 8 cm measurement (0.933) was also higher than for the 7 cm measurement (0.879). Conclusion: This research concludes that measuring hand muscle strength at the 8 cm position demonstrates greater consistency and reliability than at the 7 cm position, and is therefore recommended for use as a measurement method in research and clinical practice.